Features of using the main criterion of the FDD method in identifying the dynamic characteristics of structures - Andrianova Elena; Boldyrev Yury (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
This publication continues the series of articles devoted to the Frequency Domain Decomposition (FDD) method that serves to identify the dynamic characteristics of structures (natural frequencies and forms of natural vibrations) from the vibration tests data without using vibroexcitation. The method is based on the SV-decomposition of the cross-spectral density matrix (CSDM) of the measured signals. The proof of the possibility of using the FDD for an incomplete CSDM was given, such matrices being typical when working with large-sized structures. In this case, vibration tests include two types of measurements: continuous long-term ones taking at one or more selected reference points and consecutive short ones at other measuring points. The presented results may be useful in the operation of large concrete dams and other hydraulic structures to identify their dynamic characteristics.